Antifungal activity of neem leaf ethanol extract on Aspergillus flavus - Ayly Margaret; Hanna Yolanda; Wibisono Lies K (Universa Medicina, 2015)
BACKGROUND Aspergillosis is an infectious disease due to inhalation of Aspergillus spores. Drug resistance to aspergillosis has been reported since 14 years ago. Therefore, alternative treatment using herbals began to attract the attention of the medical profession and the community, because herbals are relatively safe and have minimal side effects. Neem (Azadirachta indica) is an herb with broad spectrum biological activity, but studies on the antifungal activity of neem leaves are lacking. The objective of this study was to evaluate the activity of neem leaves on Aspergillus flavus (A. flavus). METHODS This was a laboratory experimental study using A. flavus samples obtained from bronchial washing specimens of inpatients. Neem leaf extract in ethanol (NLE) was prepared in various concentrations. Aspergillus. flavus antifungal activity of NLE were assessed by disc diffusion (using NLE at 1.0; 0.75; 0.50; 0.25 g/dL) and macrodilution (using NLE at 1.0; 0.75; 0.5; 0.25; 0.125 g/dL). Ketoconazole 0.1 g/dL was used as antifungal positive control. Disc diffusion and macrodilution were conducted using Sabouraud dextrose agar and broth, to measure inhibition zone diameter and minimal inhibitory concentration (MIC), respectively. Statistical analysis was performed using Mann-Whitney test from SPSS 15. RESULTS There were significant differences in inhibition zone diameter (p = 0.034) between A. flavus samples exposed to NLE (1 g/dL) and the control group exposed to ketoconazole (0.1 g/dL). The MIC of NLE against A. flavus was 0.5 g/dL. CONCLUSIONS Neem leaf ethanol extract has antifungal activity against A.flavus in vitro.